2011
DOI: 10.1080/10438591003668646
|View full text |Cite
|
Sign up to set email alerts
|

Filing strategies and patent value

Abstract: This paper aims at contributing to the literature on the determinants of patent value. First, it puts forward a new potential class of value determinants in the form of filing strategies (encompassing filing routes and drafting styles). Second, it provides empirical evidence suggesting that these strategies are consistently and positively associated with patent value indicators. The empirical implementation relies on a unique dataset (about 250,000 patents granted by the EPO), which allows running large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Firms are inclined to patent valuable inventions, which has inspired numerous studies on factors that affect firms' patenting strategies and on the likelihood of patent granting (Ernst, 1995;Granstrand, 1999;Kortum and Lerner, 1999;van Zeebroeck and van Pottelsberghe, 2011). Arundel and Kabla (1998) and Brouwer and Kleinknecht (1999), for instance, found that factors such as firm size, R&D collaborations, and sector differences have various impacts on a firm's propensity to patent.…”
Section: An Integrated Two-factor Patenting Behavior Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…Firms are inclined to patent valuable inventions, which has inspired numerous studies on factors that affect firms' patenting strategies and on the likelihood of patent granting (Ernst, 1995;Granstrand, 1999;Kortum and Lerner, 1999;van Zeebroeck and van Pottelsberghe, 2011). Arundel and Kabla (1998) and Brouwer and Kleinknecht (1999), for instance, found that factors such as firm size, R&D collaborations, and sector differences have various impacts on a firm's propensity to patent.…”
Section: An Integrated Two-factor Patenting Behavior Frameworkmentioning
confidence: 98%
“…Graham and Sichelman (2008) summarized nine rationales for start-up firms to patent: (1) maintaining a supra-competitive price, (2) generating licensing revenues, (3) developing an arsenal for cross-licensing, (4) securing investments and financing, (5) using patents as shields, (6) engaging in patent bullying, (7) blocking and preemptive patenting, (8) substituting patents for non-disclosure agreements, and (9) validating an inventor's ideas. Given the benefits of patenting, firms are inclined to patent valuable inventions, which lead to a stream of studies investigating factors that affect a firm's patenting strategy, and the likelihood of receiving a grant award (Ernst, 1995;Granstrand, 1999;van Pottelsberghe, 2000, 2002;Kortum and Lerner, 1999;van Zeebroeck and van Pottelsberghe, 2011). Their pioneering work of van Pottelsberghe (2000, 2002) found that Patent Cooperation Treaty (PCT) route, technological diversity, domestic and international R&D collaborations and/or co-applications, and the mix of designated states for protection (i.e., different countries where an invention is protected) (Guellec and van Pottelsberghe, 2000), increase the probability for patents to be granted.…”
Section: Patenting or Not Patentingmentioning
confidence: 99%
“…We use a method similar to that of Guellec and van Pottelsberghe de la Potterie (2001) 5 Patent claims are a series of numbered expressions describing the invention in technical terms and defining the extent of the protection conferred by a patent (the legal scope of the patent). A high number of patent claims is an indication that an innovation is broader, has a greater potential profitability and is indicative of higher patent value (Tong and Frame, 1994;van Zeebroeck and van Pottelsberghe de la Potterie, 2006). However, there are some shortcomings related to the use of claims as a patent quality indicator as well.…”
Section: [Insert Table 1 Near Here]mentioning
confidence: 99%
“…Much of the empirical literature studying patent process delay is descriptive, as it is primarily aimed at measuring the degree of association between delay and value, and other components of a firm's strategy. A parallel empirical literature puts measures of patent value on the left-hand side of the equation, and lists on the right-hand side variables intended to capture certain aspects of filing strategy, including aspects of the strategy that delay the patent process (Guellec and van Pottelsberghe, 2000;van Zeebroeck and van Pottelsberghe, 2011a). 26 Some attention has been given to the impact of delay on other aspects of an innovator's patenting strategy.…”
Section: Filing Strategiesmentioning
confidence: 99%